CUSTOMER EXPERIENCE SEBAGAI MEDIASI PENGARUH MULTI HALAL FRIENDLY-HOTEL ATRIBUTES TERHADAP KEPUASAN PELANGGAN GRAND MADANI HOTEL MATARAM - Muhamad Ma'ruf .; Dwi Putra Buana Sakti; Handry Sudiartha Athar (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
This study aims to analyze the effect of multi halal friendly hotel attributes on customer satisfaction at Grand Madani Hotel Mataram, West Nusa Tenggara Province, Indonesia using associative quantitative methods. In this study, the population is all hotel guests who have stayed at the Grand Madani Hotel Mataram. The number of samples used in this study were 105 samples using nonprobability sampling. The data used in this study are primary and secondary data. Data collection was done using a questionnaire / google form. Data analysis using path analysis using SEM AMOS Version 24 as a data processing tool. The results of this study indicate that: 1. Multi halal friendly hotel attributes have no significant effect on customer experience; 2. Customer experience has a significant effect on customer satisfaction 3. Multi halal friendly hotel attributes have no significant effect on customer satisfaction; 4. Multi halal friendly hotel attributes have a significant positive effect on customer satisfaction after going through the customer experience intervening variable.Keywords:Multi halal friendly hotel attributes; customer experience; customer satisfaction; sharia hotel